Adenoid (Acantholytic) Squamous Cell Carcinoma of Mandibular Gingiva. (23rd July 2021) - Raut, T.; Keshwar, S.; Jaisani, M. R.; Shrestha, A.
Abstract : Introduction . Adenoid (acantholytic) squamous cell carcinoma (ASCC) is a histological variant of squamous cell carcinoma which occurs mainly in the sun-exposed areas of the head and neck region. It is commonly seen among males which mainly occurs in the sixth and seventh decade of life with lip being predominately affected. Limited scientific literature is documenting the intraoral presentation of ASCC in contrast to its usual extraoral lesions associated with the skin. Characteristic pseudo glandular alveolar space formation seen in ASCC often mimics carcinoma of salivary gland origin. In-depth knowledge of histopathological features of ASCC is important to diagnose this uncommon variant. Case Description . An 80-year-old female presented with the chief complaint of the nonhealing lesion in the right lower back region of the jaw for 2 months, associated with pain. A provisional diagnosis of oral cancer was considered, and an incisional biopsy was done. Histopathological presentation of the epithelial tumor island, pseudo glandular duct-like structures, and neoplastic cells showing features of dysplasia and keratin pearl formation confirmed the diagnosis as adenoid (acantholytic) squamous cell carcinoma. Conclusion . The histopathological presentation of adenoid (acantholytic) squamous cell carcinoma reflects the prognosis and metastatic behavior of the diseases. The knowledge of histopathological features of ASCC would be a guide to the untrained eye for the diagnosis and management of this uncommon variant to minimize the rate of metastasis or reoccurrence.